An Insight into the Psychological Issues of Indigenous Women through First Nations Theatre - T., H. Samjaila; Gayathri, N. (International Journal of Psychosocial Rehabilitation, 2020)
Many indigenous people in Canada have been victims of forced dispersal to various parts of the United States on account of the cultural erasure scheme endorsed by colonizers. They undergo acute pain and sufferings due to various atrocities and violence against them. This study explores the significance of First Nations theatre, which unravels the lives of many Indigenous children who have been ripped off from their communities and displaced to different foster homes. Given the various forms of discrimination in terms of the settler’s cohesive policy making, the lack of adequate facilities at present, the study interrogates the assumptions of the “Imaginary Indian” propagated by the colonial discourse. With the implications of articles and texts on First Nations theatre, the study seeks to explicate and contextualize Marie Clements’ play, Tombs of the Vanishing Indian. The need to represent the real condition of Native people is vital so as to provoke social awareness and draw the attention of the world towards the hideous plot of the colonizers, which otherwise would go unnoticed. It also argues that First Nations theatre is a powerful platform of resistance against the inhuman colonial practice of cultural erasure, which affects the equilibrium of Native people’s lives. ¬ The study finds that First Nations theatre inculcates reality on stage so as to pave way for social change and to find a better space for the Indigenous people of the land.